Clinical significance of presenting syndromes on outcome after coronary artery bypass grafting. (12th November 2019) - Bin Mahmood, Syed Usman; Mori, Makoto; Yousef, Sameh; Mullan, Clancy W; Mangi, Abeel A; Geirsson, Arnar
Abstract: OBJECTIVES: Evidence of an association between postoperative survival and the presenting syndrome following coronary artery bypass grafting (CABG) is limited. Our goal was to evaluate whether the presenting symptoms of acute coronary syndrome (ACS) or stable ischaemic heart disease were associated with mid-term survival in patients undergoing CABG. METHODS: We performed a single-centre retrospective study involving consecutive CABG operations from 2011 to 2016. Post-discharge survival was ascertained via patient-level data linkage with the State of Connecticut vital statistics. Baseline and postoperative variables were compared between the two groups. The multivariate Cox proportional hazard model, adjusted for demographics and comorbidity, was used to show whether the presenting syndrome category was independently associated with mid-term survival. RESULTS: A total of 1631 patients were included: 794 with stable ischaemic heart disease and 837 with ACS. Patients with ACS who underwent CABG showed more comorbidities. The overall 30-day mortality rate was 1.8% (ACS 2.3% vs stable ischaemic heart disease 1.3%; P  = 0.12). In-hospital, postoperative outcomes revealed higher rates of prolonged ventilation (11.7% vs 4.8%; P  < 0.001), pneumonia (6.6% vs 3.9%; P  = 0.016) and stay in the intensive care unit (3.7 ± 4.0 vs 3.2 ± 2.7 days; P  = 0.014) in patients with ACS. The overall mean duration of the long-term follow-up period was 27.9 ± 16.5 months, during which 117 deaths occurred. The multivariable Cox proportional hazard model adjusted for demographics and comorbidity showed that ACS was not a predictor of mid-term mortality [hazard ratio (HR) 1.26, 95% confidence interval (CI) 0.84–1.90; P  = 0.26]. Other significant predictors were cardiogenic shock (HR 2.12, 95% CI 1.04–4.33; P  = 0.039) and history of congestive heart failure (HR 1.78, 95% CI 1.18–2.69; P  = 0.0062). CONCLUSIONS: The presenting syndrome was not an independent predictor of the mid-term mortality rate. The results indicate that the classification of the presenting syndrome may be fluid and that clinical decision-making for postoperative care of patients who have CABG directed by category of presenting syndrome needs careful consideration. These data should be interpreted in the context of the limitations of this study.